Chronic Liver Disease: An Updated Review for Healthcare Professionals - Azizan, Shamaa Ali Faye; Alshami , Khulud Abdu Muharrq; Alnajrani, Hassan Hadi M; Alotaibi, Musaad Saeed S; Al Otaibi, Bandar Dohaim; Bahsan, Ahmed Essa Mousa; Al_Dalbahi, Fawaz Bandar Saqer; Aldhafeeei, Hadeel Khalid Ajmi; Al_Dalbahi, Fawaz Bandar Saqer; Aqeeli , Fatema Ibrahim; Thaker, Asmaa Suliman Hadi; Alshrarary, Faisal Hammoud; et al. (Journal of Ecohumanism, 2024)
Background: Chronic liver disease (CLD) is a progressive condition characterized by the deterioration of liver function over time, leading to fibrosis, cirrhosis, and potentially hepatocellular carcinoma (HCC). The liver, a vital organ, performs essential functions such as detoxification, protein synthesis, and bile production. CLD arises from various etiologies, including viral hepatitis, alcohol abuse, non-alcoholic fatty liver disease (NAFLD), autoimmune disorders, and genetic conditions. The disease progresses through stages of inflammation, fibrosis, and cirrhosis, with complications such as portal hypertension, ascites, hepatic encephalopathy, and HCC significantly impacting patient quality of life and survival. Aim: This review aims to provide healthcare professionals with an updated understanding of the etiology, pathophysiology, clinical manifestations, diagnostic approaches, and management strategies for CLD. It emphasizes the importance of early diagnosis, targeted treatment, and multidisciplinary care to improve patient outcomes. Also, this review investigated the main role of anesthesiologists during chronic liver diseases care. Methods: The review synthesizes current literature on CLD, focusing on its diverse etiologies, molecular mechanisms, and clinical progression. Diagnostic tools, including serological tests, imaging, and liver biopsy, are discussed. Management strategies, including pharmacological treatments, lifestyle modifications, and surgical interventions, are outlined. The role of scoring systems like Child-Pugh and MELD in assessing disease severity and prognosis is also highlighted. Results: CLD is a multifactorial condition with varying progression rates depending on the underlying cause. Early-stage fibrosis may be reversible, but advanced cirrhosis is irreversible without liver transplantation. Complications such as variceal bleeding, hepatic encephalopathy, and HCC significantly worsen prognosis. Advances in antiviral therapies, antifibrotic agents, and liver transplantation have improved outcomes, but early intervention remains critical. Conclusion: CLD is a complex and debilitating condition requiring a comprehensive approach to diagnosis and management. Early detection, tailored treatment, and patient education are essential to slow disease progression and improve survival. Multidisciplinary care, including hepatologists, anesthesiologists, and surgeons, plays a pivotal role in optimizing outcomes for patients with CLD.